2013
DOI: 10.1111/ppa.12035
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and genetic diversity of root‐knot nematodes (Meloidogyne spp.) in potatoes from South Africa

Abstract: A molecular-based assay was employed to analyse and accurately identify various root-knot nematodes (Meloidogyne spp.) parasitizing potatoes (Solanum tuberosum) in South Africa. Using the intergenic region (IGS) and the 28S D2-D3 expansion segments within the ribosomal DNA (rDNA), together with the region between the cytochrome oxidase subunit II (COII) and the 16S rRNA gene of the mtDNA, 78 composite potato tubers collected from seven major potato growing provinces were analysed and all Meloidogyne species pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Molecular analyses have been used for species identification in several genera of plant-parasitic nematodes, including Globodera, Pratylenchus, Meloidogyne and Radopholus (Powers, 2004;De Luca et al, 2011;Subbotin et al, 2011 ;Trinh et al, 2012;Onkendi & Moleleki, 2013). In the present study, sequence comparison of the region between 18S and 26S rDNA to those available in the public database supported the identity of the nematodes associated with the dry rot symptoms in yams and yampee in Costa Rica as S. bradys.…”
Section: Discussionsupporting
confidence: 75%
“…Molecular analyses have been used for species identification in several genera of plant-parasitic nematodes, including Globodera, Pratylenchus, Meloidogyne and Radopholus (Powers, 2004;De Luca et al, 2011;Subbotin et al, 2011 ;Trinh et al, 2012;Onkendi & Moleleki, 2013). In the present study, sequence comparison of the region between 18S and 26S rDNA to those available in the public database supported the identity of the nematodes associated with the dry rot symptoms in yams and yampee in Costa Rica as S. bradys.…”
Section: Discussionsupporting
confidence: 75%
“…Can new diagnostic tools based on molecular technology be employed together with classical methods to carry out accurate identification? For instance, Onkendi & Moleleki (,b) have recently demonstrated the use of molecular approaches in accurately identifying various Meloidogyne spp. present in potatoes from South Africa.…”
Section: Meloidogyne Species Present In Africamentioning
confidence: 99%
“…29 The importance of considering as many as possible nematode parameters when investigating aspects such as host plant resistance was highlighted as a result of this research. It is also suggested that the use of host plant resistance in only one crop (soybean in this case) in local rotation cycles with other susceptible crops such as maize 8,10 , sunflower 58 , potato 59 or dry bean 9,11 may not be sufficient for keeping M. incognita population levels below damage-threshold levels in the medium to long term. Also, the use of host-plant resistance as the only management strategy may not provide sufficient protection against nematode pests.…”
Section: Glasshouse and Semi-field Studiesmentioning
confidence: 99%